The Role of Financial Literacy for Students Personal Finances - MS Efendi; Pandary Ary yanti; Tri Hennarti Daulay; Herlina Yustati (Sharia Economic and Management Business Journal (SEMBJ), 2024)
SNLIK results show that in 2022 the financial literacy index of the country's population will be 49.68 percent, an increase compared to 2019 which was at 38.03 percent. Meanwhile, the financial participation index this year reached 85.10 percent, an increase compared to the financial participation index in the same period in 2019 which reached 76.19 percent. This implies that the literacy and inclusion gap is getting smaller from 38.16 percent in 2019 and 35.42 percent in 2022. This can happen if each student has a different way of thinking and opinions regarding finance, one of which is in responding to existing financial reports. Apart from that, there is no difference in financial management actions if seen from the average responses of respondents who have good and bad attitudes. Therefore, based on differences in previous research results, this study uses financial attitudes as an independent variable.